Social Diversity Model: Inheritance of Mutual Collaboration in the Indonesian Hindu-Muslim Society at Tengger, Lumajang - Abdul Chalim; Shohib Muslim; Sholahuddin Al-Fatih; Fadloli; Asrul Ibrahim Nur (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2023)
This study aims to describe and analyze how the cultural inheritance of a collaborative Hindu-Muslim community occurs in Tengger Village, Lumajang Regency, East Java, Indonesia using the concept of ta'âwun as the theoretical framework. The research is qualitative with a multi-case study type. Data were collected using in-depth interviews to relevant parties, participant observation at the research locus, and documentation to collect information about the history and general description of the Tengger people. Meanwhile, data analysis is by examining ta’âwun concept by presenting and condensing data then drawing conclusions. Researchers check the data validity using credibility, transferability, dependability, and confirmability. This research resulted in the following: the cultural inheritance of mutual collaboration in the community is through; 1) becoming role model to show respect on others’ right, 2) establishing and maintaining community organization, 3) organizing customary events with committees coming from the whole part of the community.